Addition of infliximab compared with addition of sulfasalazine and hydroxychloroquine to methotrexate in early rheumatoid arthritis: 2-year quality-of-life results of the randomised, controlled, SWEFOT trial. Issue 12 (29th November 2012) - Karlsson, Johan A; Neovius, Martin; Nilsson, Jan-Åke; Petersson, Ingemar F; Bratt, Johan; van Vollenhoven, Ronald F; Ernestam, Sofia; Geborek, Pierre
Abstract : Objective: To compare EuroQol 5-Dimensions (EQ-5D) utility and quality-adjusted life-years (QALYs) in patients with early, methotrexate (MTX) refractory rheumatoid arthritis (RA), randomised to addition of infliximab (IFX) or sulfasalazine and hydroxychloroquine (SSZ+HCQ). Methods: RA-patients with symptoms <1 year were enrolled between 2002 and 2005 at 15 Swedish centres. After 3–4 months of MTX monotherapy, patients with a remaining DAS28>3.2 were randomised to addition of IFX or SSZ+HCQ and followed for 21 months. EQ-5D profiles were collected every 3 months. Between-group comparisons of utility change and accumulated QALYs were performed, using last observation carried forward (LOCF) following protocol breach. Missing data were imputed by linear interpolation or LOCF. Sensitivity analyses applying baseline observation carried forward (BOCF) or restricted to completers were conducted. Results: Of 487 patients initially enrolled, 128 and 130 were randomised to IFX or SSZ+HCQ, respectively. Mean utility in the IFX and SSZ+HCQ groups increased from 0.52 (SD 0.27) and 0.55 (SD 0.27) at randomisation to 0.66 (SD 0.25) and 0.63 (SD 0.27) at 21 months (adjusted mean difference favouring IFX 0.04; 95% CI −0.01, 0.09; p=0.15). Average accumulated QALYs were 1.10 (SD 0.37) and 1.07 (SD 0.42) in the IFX and SSZ+HCQ groups, respectively (adjusted mean difference favouring IFX 0.07; 95%CI −0.01, 0.14; p=0.07). BOCF analysis showed similar results, while differences were reversed, though remained statistically non-significant among completers. Dropout rates in the IFX/SSZ+HCQ groups were 30%/43% (p=0.01). Conclusions: Comparing addition of IFX or SSZ+HCQ to MTX in active early RA, no statistically significant differences in utility or QALY gain could be detected over 21 months. Trial registration: Registered in WHO database at the Karolinska University Hospital, number CT20080004.